Performance experiments with a gas wave ejector equipped with curved channels and an analysis of the influence of channel angles. Issue 27 (16th June 2022) - Zhao, Yiming; Li, Haoran; Hu, Dapeng
Abstract : The effects of curved rotor channel for enhancing the efficiency of gas wave ejector, improving the portion of static pressure of medium-pressure gas, and reducing operating power consumption are studied by simulation and experiment. Abstract : Gas wave ejectors (GWEs) utilize pressure waves to efficiently transfer energy between gases, and they have broad applications in the chemical industry. In order to improve the performance of GWEs, the influence of bending angles on GWE performance was studied and experiments involving a GWE equipped with curved channels were carried out for the first time in this study. The research results show that when the exhaust angle difference ( φ dout ) is ≤−3.9° and the incident angle difference ( φ din ) is >5.0° or ≤−5.0°, the equipment performance decreases with an increase in the absolute values of the angle differences. The maximum efficiency of the backward-curved-channel device is 61.6% within the experimental range. The experimental efficiency of the curved-channel device and the static-pressure proportion of the total pressure of the medium-pressure gas are enhanced in comparison with a traditional straight-channel device, and the operating power consumption is relatively reduced. Due to the difference between the gas incident and exhaust angles, the manner in which the performance of the curved-channel device varies with the rotation speed is different depending on the working conditions.